Phenol degradation and molecular validation of phenol hydroxylase gene of Alcaligenes faecalis - Abdul Habib, Nur Muhamad Syahir (2015)
Currently, phenol pollution has caused some environmental concerns as it causes severe toxicity towards human health and environmental conditions. Intensive efforts to reduce the contamination of pollutants have been done especially in bioremediation techniques. Many microbial species have been introduced to be utilised for contamination clean-up and one of them is Alcaligenes faecalis. A study on the phenol degrading ability and molecular analysis of A. faecalis was conducted. To study the phenol degrading ability of A. faecalis, the bacteria was incubated in six different concentrations of phenol – 0.1, 0.4, 0.5, 0.9, 1.0, and 1.5 g/L. The growth of bacteria and phenol degradation in each phenol concentration were monitored. Among all the concentrations studied, phenol concentration of 0.9 g/L showed the highest degradation rate. Meanwhile, the molecular analysis of the bacteria was carried out by isolating the phenol hydroxylase gene which is responsible for degrading phenol by using the designated primer. The gene was amplified by using PCR technique with an annealing temperature of 56.4°C. The expected size of the gene was between 300 - 400 bp. After DNA sequencing, molecular analysis was done and the DNA fragment obtained had a length of 337 bp. Next, BLAST search was used to confirm the sequence obtained was phenol hydroxylase gene isolated from A. faecalis. The BLAST result showed that the phenol hydroxylase gene was successfully amplified from the bacteria. These studies showed the hypothetical use of this bacteria to treat phenol-contaminated environment.